Design of Automatic Fish Feeding Device Based on Arduino With RTC and Servo Motor in Ornamental Fish Pond - Maulana, Rifki; Ardelia Astriany Rizki (Politeknik Piksi Ganesha Indonesia, 2025)
Ornamental fish care requires regular feeding, but the owner's busy schedule is often an obstacle. This study aims to design an Arduino-based automatic fish feeder, using an RTC (Real Time Clock) module for time scheduling and a servo motor to drive the feeding mechanism. This system is designed to ensure that feed is given at the right time without manual intervention. The prototype of this tool was tested in an ornamental fish pond and showed satisfactory results. This tool is able to provide feed accurately according to a predetermined schedule, and the servo motor functions well in controlling feed distribution. The use of RTC has proven effective in maintaining time accuracy, ensuring that fish eating patterns remain consistent. This tool is also efficient in energy use and provides convenience for ornamental fish owners, reducing the risk of missed or excessive feeding. The results of this study indicate that this automatic feeding system can be a practical solution in ornamental fish care, with the potential to be further developed through the integration of IoT technology.